Meningkatkan Hasil Belajar IPAS Dengan Menerapkan Pendekatan Culturally Responsive Teaching (CRT) Pada Siswa Kelas IV SDN Jajartunggal 3 Surabaya - Sulastri Sulastri; Hery Setiyawan; Rizky Widyaningrum (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research is an effort to improve student learning outcomes through implementing the Culturally Responsive Teaching (CRT) approach in class IV science and science subjects at SDN Jajartunggal 3/452 Surabaya. This research is motivated by the learning outcomes of many students which are still below the KKM in science and science subjects. This research uses the Classroom Action Research (PTK) method. The research was conducted April 1-3 2024 in class IV-B at SDN Jajartunggal 3 Surabaya. The data collection techniques used are tests, documentation, interview and observation. Data analysis uses quantitative and qualitative data. The research instrument uses a test sheet. This test sheet includes a pre-test and post-test sheet. The results of the research show that learning outcomes in the realm of students' knowledge increased quite significantly between cycle I 57% and cycle II 82%. This proves that implementing the Culturally Responsive Teaching (CRT) approach can improve student learning outcomes.